The older the better: The characteristic of localized prostate cancer in Chinese men - Haifeng Wang; Xu Gao; Ziyu Fang; Xin Lu; Yan Wang; Chunfei Ma; Zhenkai Shi; Bo Yang; Shancheng Ren; Chuanliang Xu; Yinghao Sun (Asian Journal of Urology)
Objective: To assess the clinicopathological features and overall survival between two groups of Chinese patients older or younger than 70 years after retropubic radical prostatectomy. Methods: From January 2001 to February 2010, 390 patients receive dretropubic radical prostatectomy. After excluding 89 patients with adjuvant or neoadjuvant hormonal therapy or radiotherapy, a total of 301 patients were included in this study. We arbitrarily divided these patients into younger age group (<70 years, 140 cases, 46.5%) and older age group (≥70 years, 161 cases, 53.5%). The differences in serum prostate specific antigen (PSA), Gleason score, clinical tumor stage, and biochemical-free survival were analyzed between the two groups. Results: There were not significant differences between the two groups in high Gleason score rate and clinical tumor stage. However, older patients had significantly lower biochemical recurrence rate than those of younger patients, and had significantly higher PSA levels. Multivariate analysis showed that older age, PSA level and clinical tumor stage were significantly associated with biochemical recurrence free survival. Conclusion: In Chinese men, older age (≥70 years) is associated with better outcome. If the physical condition permits, older age alone should not exclude patients from radical prostatectomy.